2022
DOI: 10.2196/30464
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Player Types to Tailor Game-Based Learning Design to Learners: Cross-sectional Survey using Q Methodology

Abstract: Background Game-based learning appears to be a promising instructional method because of its engaging properties and positive effects on motivation and learning. There are numerous options to design game-based learning; however, there is little data-informed knowledge to guide the choice of the most effective game-based learning design for a given educational context. The effectiveness of game-based learning appears to be dependent on the degree to which players like the game. Hence, individual dif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…The consequence of this is the need to create educational games that dynamically adapt to the lecture content. It should also be noted that a game should be adapted to player types in order to achieve a positive effect [11].…”
Section: Serious Games In Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…The consequence of this is the need to create educational games that dynamically adapt to the lecture content. It should also be noted that a game should be adapted to player types in order to achieve a positive effect [11].…”
Section: Serious Games In Educationmentioning
confidence: 99%
“…Based on Bartle's model, Gaalen et al [11] conducted a study among medical and dental students using the Q-methodology. Participants were asked to sort 49 statements about gaming preferences based on their level of agreement.…”
Section: Player Type Researchmentioning
confidence: 99%
“…GBL is a kind of gameplay that has explicit learning objectives (Plass et al, 2015). The potential of GBL as an effective instructional method is promising due to its ability to captivate learners and positively impact their motivation and learning outcomes (Budasi et al, 2020;Loderer et al, 2019;Steinkuehler and Squire, 2014;Van Gaalen et al, 2022). Plass et al (2015) suggested a theoretical basis for incorporating games into the learning process that involved motivational, cognitive, affective, and sociocultural foundations.…”
Section: Gblmentioning
confidence: 99%
“…As recent research indicates, the effectiveness of serious games appears to be correlated to the degree to which play ers like the game (Van Gaalen et al, 2022). Hence, using a player classification in the games user research can help game designers to identify more clearly interpretable patterns and show how players perceive play to design more com pelling games.…”
Section: Gaps and Research Opportunitiesmentioning
confidence: 99%
“…Some re searchers have even searched for typological classifications in other areas, such as Psychology, Anthropology, and Soci ology, that can be used to understand the players' profiles (Paulin, 2013). More recently, researchers have started in vestigating scientifically sound approaches to identify player types, demonstrating that game effectiveness may be corre lated to player types (Van Gaalen et al, 2022).…”
Section: Introductionmentioning
confidence: 99%